High-Intensity Interval Training for Hypertension: Program Design and Application. (September 2021) - Uken, Brent; Lee, Matthew; Wright, Gage; Feito, Yuri
Apply It!: This article explores the frequency, intensity, time, and type framework within the context of HIIT, the unique elements of HIIT ( e.g., intensity and work-to-recovery ratio), and concludes with examples of HIIT exercise regimens. By reading this article, health and fitness professionals will be reminded of the following takeaways: HTN develops gradually and is generally the product of lifestyle choices concerning diet and exercise. Although HTN is routinely treated with pharmacological intervention, lifestyle intervention is a primary therapeutic option for those newly diagnosed with hypertension. Research supports the implementation of aerobically based HIIT and MICT for inducing similar reductions in systolic blood pressure and diastolic blood pressure in adults with pre-HTN and/or HTN. HIIT for any client must be introduced gradually — and deliberately — over time. The introduction of HIIT should start with a single, brief set of HIIT ( e.g., a few minutes of HIIT) to evaluate the client's readiness and receptivity to the approach.